Association of ABO Blood Group Antigen and Neurological Tumors - Gopal K. Patidar; Yashaswi Dhiman; Anjali Hazarika (Journal of Neuroanaesthesiology and Critical Care, 2022)
Background Various risk factors for tumors such as smoking, alcohol consumption, diet, and radiation, etc., were already identified. ABO blood group antigens are also present on epithelia, endothelia, and neurons. Recent evidence suggested the role of ABO antigens in the pathogenesis of certain malignancies. Materials and Methods A retrospective observational study was conducted in a tertiary care neurosurgical center in North India from January 2016 to December 2018. The hospital information system was used to obtain patient information while the blood center information system was used to collect blood group information. Brain tumors were majorly divided into cavernoma, glioma, meningioma, neuroma, pituitary adenoma, schwannoma, and others. Results We found a total of 1,970 patients with brain tumors admitted during our study period. Most patients had glioma (33.55%), followed by pituitary adenoma (20.05%) and neuroma (2.23%). B blood group individuals had more prevalence of cavernoma, glioma, meningioma, pituitary adenoma, schwannoma, and others followed by O, A, and AB. Only association of O blood group with neuroma tumor was found statistically significant. Conclusions Our patient population had blood group distribution similar to our general population and no significant association was observed by blood group antigens and brain tumors. Although neuroma was significantly associated with blood group O but the prevalence of neuroma in our patient population is very low hence large sample study is required to draw a firm conclusion regarding this association.